Lithium-ion conducting oxides and solid-state batteries

A lithium ion conductive oxide with specific elemental ratios and a confirmed crystal structure addresses the challenge of achieving high relative density and conductivity, enhancing all-solid-state battery performance.

JP7613567B2Active Publication Date: 2025-01-15RESONAC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023517140
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-28
Filing Date
2022-03-17
Publication Date
2025-01-15
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

Conventional lithium ion conductive oxides face challenges in achieving high relative density and sufficient ionic conductivity, which are essential for effective use in all-solid-state batteries, and existing oxide-based solid electrolytes are not easily obtainable with high relative density.

Method used

A lithium ion conductive oxide composition based on LiTa2PO8 with specific elemental ratios of lithium, tantalum, boron, phosphorus, and fluorine, optionally including niobium, is developed to achieve a relative density of 70% or more and sufficient ionic conductivity, utilizing a crystal structure that can be confirmed by XRD analysis.

Benefits of technology

The developed oxide achieves a high relative density and total ionic conductivity, enabling improved performance in all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613567000003
    Figure 0007613567000003
  • Figure 0007613567000001
    Figure 0007613567000001
  • Figure 0007613567000002
    Figure 0007613567000002
Patent Text Reader

Abstract

One embodiment of the present invention pertains to a lithium ion conducting oxide or an all solid battery, said lithium ion conducting oxide having a crystal structure based on LiTa2PO8, containing at least lithium, tantalum, boron, phosphorus, oxygen and fluorine as the constituent elements thereof, having a boron content represented by formula (1) of 4.0-15.0%, and having a fluorine content represented by formula (2) of 0.5-2.0%. (1): Number of B atoms / (number of B atoms + number of P atoms) × 100 (2): Number of F atoms / (number of O atoms + number of F atoms) × 100
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] One embodiment of the present invention relates to a lithium ion conducting oxide or all-solid-state battery. [Background technology]

[0002] In recent years, there has been a demand for the development of high-output, high-capacity batteries as power sources for laptops, tablet computers, mobile phones, smartphones, electric vehicles (EVs), etc. Among these, all-solid-state batteries that use solid electrolytes instead of liquid electrolytes such as organic solvents have attracted attention as batteries with excellent charge / discharge efficiency, charging speed, safety, and productivity.

[0003] As the solid electrolyte, inorganic solid electrolytes have been attracting attention, and as the inorganic solid electrolytes, mainly oxide-based and sulfide-based solid electrolytes are known. Although the use of sulfide-based solid electrolytes has the advantage that batteries can be produced by cold pressing or the like, they are unstable when exposed to humidity and may generate harmful hydrogen sulfide gas. For this reason, the development of oxide-based solid electrolytes (e.g., Patent Documents 1 to 3) is being promoted from the standpoint of safety, etc. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-157090 A [Patent Document 2] International Publication No. 2020 / 036290 [Patent Document 3] JP 2020-194773 A Summary of the Invention [Problem to be solved by the invention]

[0005] Oxide-based solid electrolytes (lithium ion conductive oxides) have extremely high grain boundary resistance, and in order to obtain ionic conductivity sufficient for use in all-solid-state batteries, it is necessary not only to compress and mold the lithium ion conductive oxide powder but also to sinter it to increase the relative density (the percentage of actual density compared to theoretical density). However, with the conventional lithium ion conductive oxides described in the above Patent Documents 1 to 3, it was not easy to obtain an oxide with a high relative density, and there was room for improvement in terms of ion conductivity.

[0006] An embodiment of the present invention provides a lithium ion conductive oxide that can have a high relative density and has sufficient ionic conductivity. [Means for solving the problem]

[0007] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by the following configuration examples, and have thus completed the present invention. A configuration example of the present invention is as follows.

[0008] [1] It has a crystal structure based on LiTa2PO8, At least lithium, tantalum, boron, phosphorus, oxygen and fluorine are contained as constituent elements, The content of boron represented by the following formula (1) is 4.0 to 15.0%, The content of fluorine represented by the following formula (2) is 0.5 to 2.0%. Lithium ion conducting oxide. Number of B atoms / (Number of B atoms + Number of P atoms)×100 (1) Number of F atoms / (number of O atoms + number of F atoms) × 100 (2)

[0009] [2] Furthermore, it contains niobium as a constituent element. The niobium content represented by the following formula (3) is more than 0% and not more than 20.0%. [1] The lithium ion conductive oxide according to the present invention. Number of Nb atoms / (Number of Nb atoms + Number of Ta atoms) × 100 (3)

[0010] [3] The lithium ion conductive oxide according to [1] or [2], which has a relative density, which is the percentage of the ratio of the measured density calculated from the mass and volume of the oxide to the theoretical density of the lithium ion conductive oxide, of 70% or more.

[0011] [4] The lithium ion conductive oxide according to any one of [1] to [3], wherein the content of the crystal structure based on LiTa2PO8 is 85% or more.

[0012] [5] The lithium content represented by the following formula (4) is more than 0.9 and not more than 1.5: The lithium ion conductive oxide according to any one of [1] to [4]. Number of Li atoms / {(number of Nb atoms + number of Ta atoms) / 2} (4)

[0013] [6] A positive electrode having a positive electrode active material; a negative electrode having a negative electrode active material; a solid electrolyte layer between the positive electrode and the negative electrode; Including, The solid electrolyte layer contains the lithium ion conductive oxide according to any one of [1] to [5]. All-solid-state battery.

[0014] [7] The positive electrode active material is LiM3PO4 [M3 is one or more elements selected from the group consisting of Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O. ], LiM5VO4 [M5 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al and Ti. ], Li2M6P2O7 [M6 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O. ], LiVP2O7, Li x7 V y7 M7 z7 [2≦x7≦4, 1≦y7≦3, 0≦z7≦1, 1≦y7+z7≦3, M7 is one or more elements selected from the group consisting of Ti, Ge, Al, Ga, and Zr.], Li1+x8 Al x8 M8 2-x8 (PO4)3 [0≦x8≦0.8, M8 is one or more elements selected from the group consisting of Ti and Ge. ], LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4 and Li4Ti5O 12 The all-solid-state battery according to [6], comprising one or more compounds selected from the group consisting of:

[0015] [8] The negative electrode active material is LiM3PO4 [M3 is one or more elements selected from the group consisting of Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O. ], LiM5VO4 [M5 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al and Ti. ], Li2M6P2O7 [M6 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O. ], LiVP2O7, Li x7 V y7 M7 z7 [2≦x7≦4, 1≦y7≦3, 0≦z7≦1, 1≦y7+z7≦3, M7 is one or more elements selected from the group consisting of Ti, Ge, Al, Ga, and Zr.], Li 1+x8 Al x8 M8 2-x8 (PO4)3 [0≦x8≦0.8, M8 is one or more elements selected from the group consisting of Ti and Ge. ], (Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1-y9 M10 y9 )O4 [M9 is one or more elements selected from the group consisting of Mg, Al, Ga, and Zn, M10 is one or more elements selected from the group consisting of Zn, Al, Ga, Si, Ge, P, and Ti, 0≦x9≦1.0, 0≦y9≦0.6, a9 is the average valence of M9, and b9 is the average valence of M10], LiNb2O7, Li4Ti5O 12 , Li4Ti5PO12 The all-solid-state battery according to [6] or [7], comprising one or more compounds selected from the group consisting of TiO2, LiSi and graphite.

[0016] [9] The all-solid-state battery according to any one of [6] to [8], wherein the positive electrode and the negative electrode contain the lithium ion conductive oxide according to any one of [1] to [5]. Effect of the Invention

[0017] According to one embodiment of the present invention, it is possible to provide a lithium ion conductive oxide having a high relative density and sufficient ion conductivity. [Brief description of the drawings]

[0018] [Figure 1] 1 shows XRD patterns of the lithium ion conductive oxides obtained in Examples 2 and 3 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] <Lithium ion conductive oxide> The lithium ion conductive oxide according to one embodiment of the present invention (hereinafter also referred to as "the present oxide") has a crystal structure based on LiTa2PO8 (hereinafter also referred to as "LTPO structure"). At least lithium, tantalum, boron, phosphorus, oxygen and fluorine are contained as constituent elements, The content of boron represented by the following formula (1) is 4.0 to 15.0%, The content of fluorine represented by the following formula (2) is 0.5 to 2.0%. Boron content = number of B atoms / (number of B atoms + number of P atoms) × 100 (1) Fluorine content = number of F atoms / (number of O atoms + number of F atoms) × 100 (2)

[0020] Whether the present oxide has the LTPO structure can be determined by analyzing an X-ray diffraction (XRD) pattern, specifically, an XRD pattern measured by the method described in the examples below.

[0021] The constituent elements of the present oxide are not particularly limited as long as they include lithium, tantalum, boron, phosphorus, oxygen, and fluorine. However, it is also preferable that the oxide further includes niobium, since this makes it possible to easily obtain a lithium ion conductive oxide having a high relative density. The oxide may further include one or more other elements M selected from the group consisting of Zr, Ga, Sn, Hf, Bi, W, Mo, Si, Al, and Ge.

[0022] The content of boron in the present oxide represented by the above formula (1) is 4.0% or more, preferably 9.0% or more, and 15.0% or less, preferably 10.0% or less. When the boron content is within the above range, the oxide has a higher relative density.

[0023] The fluorine content in the present oxide represented by the above formula (2) is 0.5% or more, preferably 0.6% or more, and 2.0% or less, preferably 1.9% or less. When the fluorine content is within the above range, the oxide has a higher total ion conductivity.

[0024] When the present oxide further contains niobium element, the content of niobium represented by the following formula (3) is preferably more than 0% and not more than 20.0%. The lower limit of the niobium content is more preferably 5%. The upper limit of the niobium content is more preferably 15.0%, further preferably 12.0%, and particularly preferably 10.0%. Niobium content = number of Nb atoms / (number of Nb atoms + number of Ta atoms) × 100 (3) When the niobium content is within the above range, the oxide has a relatively high total ion conductivity and a higher relative density.

[0025] The lower limit of the lithium content in the oxide, represented by the following formula (4), is preferably more than 0.9, more preferably 1.0, and even more preferably 1.1. The upper limit of the lithium content is preferably 1.5, and more preferably 1.2. In the following formula (4), "(number of Nb atoms + number of Ta atoms)" is "number of Ta atoms" when the oxide does not have niobium as a constituent element. Lithium content = number of Li atoms / {(number of Nb atoms + number of Ta atoms) / 2} (4) When the lithium content is within the above range, the oxide has a relatively high total ion conductivity and a higher relative density.

[0026] The content of each element in the present oxide can be measured by the absolute intensity quantitative method of Auger electron spectroscopy (AES) using a standard powder sample containing Mn, Co, and Ni in a ratio of 1:1:1 as a lithium-containing transition metal oxide such as LiCoO2. It can also be determined by conventionally known quantitative analysis. For example, after adding an acid to the present oxide and pyrolyzing it, the pyrolyzate is measured in volume, and the content of each element in the present oxide can be determined using a high-frequency inductively coupled plasma (ICP) emission spectrometer.

[0027] The composition of the oxide can be adjusted simply by mixing raw materials containing the respective constituent elements so that the ratio of the contents of the respective constituent elements falls within a desired range. Specifically, as shown in the examples, the composition can be adjusted by weighing and using raw materials containing the respective constituent elements so as to satisfy a predetermined stoichiometric ratio.

[0028] The relative density of the present oxide is preferably 70% or more, more preferably 80% or more, further preferably 90% or more, and particularly preferably 95% or more.

[0029] The relative density is a percentage obtained by dividing the actual density calculated from the mass and volume of the oxide by the theoretical density of the oxide (actual density / theoretical density x 100), and specifically, it can be measured by the method described in the examples below. The theoretical density of the oxide is specifically calculated by weighting the theoretical density of the crystal structure constituting the lithium ion conductive oxide and the content of the crystal structure. For example, when the oxide has a crystal structure 1 with a content of h% and a crystal structure 2 with a content of k%, the theoretical density can be calculated as (theoretical density of crystal structure 1×h+theoretical density of crystal structure 2×k) / 100. More specifically, it can be expressed by the following formula (5). {(theoretical density of observed crystals × crystallinity (%))} / 100 (5)

[0030] The content (crystallinity) of each crystal structure can be determined by Rietveld analysis. The crystal structures contained in this oxide other than the LTPO structure include LiTa3O8, Ta2O5, and TaPO5, etc. These crystal structures can be confirmed in the XRD pattern. The oxide preferably contains an LTPO structure and at least one crystal selected from LiTa3O8, Ta2O5, and TaPO5, and more preferably contains an LTPO structure and one or two crystals selected from LiTa3O8, Ta2O5, and TaPO5. In the latter case, the content of one or two crystals selected from LiTa3O8, Ta2O5, and TaPO5 is 0%.

[0031] The content of the LTPO structure in this oxide [crystallinity of the LTPO structure] (=crystalline amount of LTPO×100 / total crystalline amount of all confirmed crystals) is preferably 85% or more, more preferably 89% or more, even more preferably 90% or more, and particularly preferably more than 95%. There is no particular upper limit to the crystalline ratio of the LTPO structure, but it is preferably less than 100%, more preferably 99% or less. When the crystallinity of the LTPO structure in the present oxide is within the above range, the oxide tends to have high total ionic conductivity.

[0032] The crystallinity of the LTPO structure in this oxide can be calculated, for example, by subjecting the XRD pattern of this oxide to Rietveld analysis using the known analytical software RIETAN-FP (available from the creator; Fujio Izumi's homepage "RIETAN-FP·VENUS system distribution file" (http: / / fujioizumi.verse.jp / download / download.html)).

[0033] When the oxide contains LiTa3O8 crystals, the upper limit of the content of LiTa3O8 crystals in the oxide (LiTa3O8 crystallinity) is preferably 12.0% or less, and the lower limit is preferably more than 1.2%, more preferably 1.5% or more, and even more preferably 3.0% or more. When the present oxide contains Ta2O5 crystals, the lower limit of the content of Ta2O5 crystals in the present oxide (Ta2O5 crystallinity) is preferably more than 0%, and the upper limit is preferably 2.5% or less, more preferably 1.5% or less, and even more preferably 1.0% or less. When the present oxide contains TaPO5 crystals, the upper limit of the content of TaPO5 crystals in the present oxide (TaPO5 crystallinity) is preferably 3.5% or less, more preferably 3.0% or less, and the lower limit is more than 0%. When at least one of the ranges of LiTa3O8 crystallinity, Ta2O5 crystallinity, and TaPO5 crystallinity is satisfied, a lithium ion conductive oxide having high relative density and / or total ionic conductivity tends to be easily obtained. In addition, when the present oxide contains at least one crystal selected from LiTa3O8, Ta2O5, and TaPO5, it is preferable that the remainder of the total crystallinity of these crystals (100 - the total crystallinity of these crystals) is the content of the LTPO structure. The crystallinity of the crystal structures of LiTa3O8, Ta2O5, TaPO5, etc. can be calculated in the same manner as the calculation of the content of the LTPO structure.

[0034] Although the present oxide basically does not contain any amorphous matter, there is no problem if the amorphous matter is contained within a range that does not affect the conductivity.

[0035] The total ionic conductivity of the oxide is preferably 2.00×10 -4 S cm -1 More preferably, 3.00×10 -4 S cm -1 More preferably, 4.00×10 -4 S cm -1 That's all. When the total ionic conductivity is within the above range, the present oxide can be said to have sufficient ionic conductivity. Specifically, the total ionic conductivity can be measured by the method described in the following examples.

[0036] <Method of manufacturing this oxide> This oxide can be produced by calcining (or sintering) raw materials that are mixed so that the contents of the respective constituent elements fall within the above-mentioned ranges. Specifically, examples of such methods include (1) a method in which the raw materials are pulverized and mixed in a ball mill or a bead mill, and then fired; and (2) a method in which the raw materials are pulverized and mixed in a ball mill or a bead mill, and then compressed into a predetermined shape and then sintered. Also included is a method (3) in which the fired product obtained by the above method (1) (further mixed with various additives as necessary) is pulverized, shaped by compression processing such as press molding, and then sintered.

[0037] As the raw material, for example, a compound containing a lithium atom, a compound containing a tantalum atom, a compound containing a boron atom, a compound containing a phosphorus atom, and a compound containing a fluorine atom are used. When the present oxide has niobium as a constituent element, a compound containing a niobium atom is further used. When the present oxide has the other element M, a compound containing an M atom is further used.

[0038] Examples of compounds containing lithium atoms include lithium carbonate (Li2CO3), lithium oxide (Li2O), lithium hydroxide (LiOH), lithium acetate (LiCH3COO), and hydrates thereof. Among these, lithium carbonate, lithium hydroxide, and lithium acetate are preferred because they are easily decomposed and reacted. The lithium atom-containing compound may be used alone or in combination of two or more kinds.

[0039] Examples of compounds containing tantalum atoms include tantalum pentoxide (Ta2O5) and tantalum nitrate (Ta(NO3)5). Among these, tantalum pentoxide is preferred from the viewpoint of cost. The compound containing a tantalum atom may be used alone or in combination of two or more kinds.

[0040] Examples of compounds containing boron atoms include LiBO2, LiB3O5, Li2B4O7, and Li3B 11 O 18 , Li3BO3, Li3BO 12 , Li4B2O5, Li6B4O9, Li 3-x5 B 1-x5 C x5 O3(0 <x5<1)、Li 4-x6 B 2-x6 C x6 O5(0 <x6<2)、Li 2.4 Al 0.2 BO3, Li 2.7 Al 0.1 Examples include BO3, B2O3, and H3BO3. The compound containing a boron atom may be used alone or in combination of two or more.

[0041] As the compound containing a phosphorus atom, a phosphate is preferable. As the phosphate, for example, diammonium hydrogen phosphate ((NH4)2HPO4) and monoammonium dihydrogen phosphate (NH4H2PO4) can be mentioned because they are easily decomposed and reacted. The compound containing a phosphorus atom may be used alone or in combination of two or more kinds.

[0042] Examples of compounds containing fluorine atoms include LiF, TaF5, NbF5, HBF4, and H2SiF6. From the viewpoints of ease of handling and ease of adjusting the composition, LiF is preferred. The fluorine atom-containing compound may be used alone or in combination of two or more kinds.

[0043] Examples of compounds containing niobium atoms include Nb2O5, LiNbO3, LiNb3O8, and NbPO5. The compound containing a niobium atom may be used alone or in combination of two or more kinds.

[0044] Examples of compounds containing M atoms include oxides and nitrates of element M. The compound containing an M atom may be used alone or in combination of two or more kinds.

[0045] The firing temperature in the method (1) is preferably 500° C. or higher, more preferably 700° C. or higher, and preferably 1200° C. or lower, more preferably 1000° C. or lower, and the firing time is, for example, 1 to 16 hours. By such firing, impurities that may be contained in the raw materials are volatilized and removed, and the desired oxide can be obtained.

[0046] The pressure during compression in the above methods (2) and (3) is not particularly limited, but is preferably 50 MPa or more, more preferably 100 MPa or more, and is preferably 500 MPa or less, more preferably 400 MPa or less. The predetermined shape is not particularly limited, but is preferably a shape suited to the intended use of the oxide, and more particularly, the solid electrolyte. In the above methods (2) and (3), the sintering temperature is preferably 600 to 1200° C., and the sintering time is, for example, 1 to 96 hours.

[0047] The firing or sintering may be performed in air, or in an atmosphere of nitrogen gas and / or argon gas with an oxygen gas content adjusted to a range of 0 to 20% by volume, or in an atmosphere of a reducing gas such as a nitrogen-hydrogen mixed gas containing a reducing gas such as hydrogen gas. As the reducing gas, ammonia gas, carbon monoxide gas, etc. may be used in addition to hydrogen gas.

[0048] ≪All-solid-state battery≫ An all-solid-state battery according to one embodiment of the present invention (hereinafter also referred to as "the battery") includes a positive electrode having a positive electrode active material, a negative electrode having a negative electrode active material, and a solid electrolyte layer between the positive electrode and the negative electrode, and the solid electrolyte layer includes the present oxide. The present battery may be a primary battery or a secondary battery, but from the viewpoint of better exerting the effects of the present invention, it is preferable that it is a secondary battery, and it is more preferable that it is a lithium ion secondary battery. The structure of the present battery is not particularly limited as long as it includes a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode, and may be any of a so-called thin film type, a laminate type, and a bulk type.

[0049] <Solid electrolyte layer> The solid electrolyte layer is not particularly limited as long as it contains the present oxide, and may contain, if necessary, a conventionally known additive used in the solid electrolyte layer of an all-solid-state battery, but is preferably made of the present oxide. The thickness of the solid electrolyte layer may be appropriately selected depending on the structure of the battery to be formed (such as a thin film type), but is preferably 50 nm or more, more preferably 100 nm or more, and is preferably 1000 μm or less, more preferably 100 μm or less.

[0050] <Positive electrode> The positive electrode is not particularly limited as long as it has a positive electrode active material, but a preferred positive electrode is one having a positive electrode current collector and a positive electrode active material layer.

[0051] [Cathode active material layer] The positive electrode active material layer is not particularly limited as long as it contains a positive electrode active material, but it preferably contains a positive electrode active material and a solid electrolyte, and may further contain additives such as a conductive assistant and a sintering assistant. The thickness of the positive electrode active material layer may be appropriately selected depending on the structure of the battery to be formed (e.g., thin film type), but is preferably 10 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, and is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less.

[0052] ·Cathode active material Examples of the positive electrode active material include LiCo oxide, LiNiCo oxide, LiNiCoMn oxide, LiNiMn oxide, LiMn oxide, LiMn-based spinel, LiMnNi oxide, LiMnAl oxide, LiMnMg oxide, LiMnCo oxide, LiMnFe oxide, LiMnZn oxide, LiCrNiMn oxide, LiCrMn oxide, lithium titanate, lithium metal phosphate, transition metal oxide, titanium sulfide, graphite, hard carbon, transition metal-containing lithium nitride, silicon oxide, lithium silicate, lithium metal, lithium alloy, Li-containing solid solution, and lithium-storing intermetallic compound. Among these, LiNiCoMn oxide, LiNiCo oxide, and LiCo oxide are preferred, and LiNiCoMn oxide is more preferred, because they have good affinity with the solid electrolyte, an excellent balance of macro-conductivity, micro-conductivity, and ion conductivity, have a high average potential, and can increase the energy density and battery capacity in terms of the balance between specific capacity and stability. The surface of the positive electrode active material may be coated with an ion-conductive oxide such as lithium niobate, lithium phosphate, or lithium borate. The positive electrode active material layer may contain one type of positive electrode active material, or two or more types of positive electrode active materials.

[0053] Suitable examples of the positive electrode active material include LiM3PO4 [M3 is one or more elements selected from the group consisting of Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O. ], LiM5VO4 [M5 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al and Ti. ], Li2M6P2O7 [M6 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O. ], LiVP2O7, Li x7 V y7 M7 z7 [2≦x7≦4, 1≦y7≦3, 0≦z7≦1, 1≦y7+z7≦3, M7 is one or more elements selected from the group consisting of Ti, Ge, Al, Ga, and Zr.], Li 1+x8 Al x8 M8 2-x8 (PO4)3 [0≦x8≦0.8, M8 is one or more elements selected from the group consisting of Ti and Ge. ], LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4, Li4Ti5O 12 Other examples include:

[0054] The positive electrode active material is preferably in the form of particles, and the 50% diameter in the volumetric particle size distribution is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.4 μm or more, particularly preferably 0.5 μm or more, and is preferably 30 μm or less, more preferably 20 μm or less, even more preferably 10 μm or less, particularly preferably 3 μm or less. The ratio of the major axis length to the minor axis length (major axis length / minor axis length), ie, the aspect ratio, of the positive electrode active material is preferably less than 3, and more preferably less than 2.

[0055] The positive electrode active material may form secondary particles, in which case the 50% diameter in the number-based particle size distribution of the primary particles is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.4 μm or more, particularly preferably 0.5 μm or more, and is preferably 20 μm or less, more preferably 15 μm or less, even more preferably 10 μm or less, particularly preferably 2 μm or less.

[0056] The content of the positive electrode active material in the positive electrode active material layer is preferably 20% by mass or more, more preferably 30% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less. When the content of the positive electrode active material is within the above range, the positive electrode active material functions favorably, and a battery with high energy density tends to be easily obtained.

[0057] ·Solid electrolyte The solid electrolyte that can be used in the positive electrode active material layer is not particularly limited, and any conventionally known solid electrolyte can be used. However, it is preferable to use the present oxide in order to better exhibit the effects of the present invention. The solid electrolyte used in the positive electrode active material layer may be one type or two or more types.

[0058] Additives Suitable examples of the conductive assistant include metal materials such as Ag, Au, Pd, Pt, Cu, and Sn, and carbon materials such as acetylene black, ketjen black, carbon nanotubes, and carbon nanofibers. As the sintering aid, a compound containing a boron atom, a compound containing a niobium atom, or a compound containing an M atom (examples of M: bismuth, silicon) is preferable. The additives used in the positive electrode active material layer may each be of one type or two or more types.

[0059] ·Positive electrode current collector The positive current collector is not particularly limited as long as its material conducts electrons without causing an electrochemical reaction. Examples of the material of the positive current collector include simple metals such as copper, aluminum, and iron, alloys containing these metals, and conductive metal oxides such as antimony-doped tin oxide (ATO) and indium tin oxide (ITO). In addition, as the positive current collector, a current collector provided with a conductive adhesive layer on the surface of a conductor can also be used. Examples of the conductive adhesive layer include a layer containing a granular conductive material, a fibrous conductive material, and the like.

[0060] <Negative electrode> The negative electrode is not particularly limited as long as it has a negative electrode active material, but preferably, a negative electrode having a negative electrode current collector and a negative electrode active material layer can be mentioned.

[0061] [Negative electrode active material layer] The negative electrode active material layer is not particularly limited as long as it contains a negative electrode active material, but preferably contains a negative electrode active material and a solid electrolyte, and may further contain additives such as a conductive aid and a sintering aid. The thickness of the negative electrode active material layer may be appropriately selected according to the structure of the battery to be formed (such as a thin film type), but is preferably 10 μm or more, more preferably 30 μm or more, still more preferably 50 μm or more, and preferably 200 μm or less, more preferably 150 μm or less, still more preferably 100 μm or less.

[0062] ·Negative electrode active material Examples of the negative electrode active material include lithium alloys, metal oxides, graphite, hard carbon, soft carbon, silicon, silicon alloys, silicon oxides SiO n (0 < n ≤ 2), silicon / carbon composites, composites in which silicon is encapsulated in the pores of porous carbon, lithium titanate, and graphite coated with lithium titanate. Among these, silicon / carbon composites and composites containing silicon domains in the pores of porous carbon are preferred because they have a high specific capacity and can increase the energy density and battery capacity. More preferred are composites containing silicon domains in the pores of porous carbon, which are excellent in mitigating the volume expansion associated with lithium absorption / release of silicon, and can maintain a good balance between macro-conductivity, micro-conductivity, and ion conductivity. Particularly preferred are composites containing silicon domains in the pores of porous carbon, in which the silicon domains are amorphous, the size of the silicon domains is 10 nm or less, and pores derived from porous carbon are present in the vicinity of the silicon domains.

[0063] Suitable examples of the negative electrode active material include LiM3PO4 [M3 is one or more elements selected from the group consisting of Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O. ], LiM5VO4 [M5 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al and Ti. ], Li2M6P2O7 [M6 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O. ], LiVP2O7, Li x7 V y7 M7 z7 [2≦x7≦4, 1≦y7≦3, 0≦z7≦1, 1≦y7+z7≦3, M7 is one or more elements selected from the group consisting of Ti, Ge, Al, Ga, and Zr.], Li 1+x8 Al x8 M8 2-x8 (PO4)3 [0≦x8≦0.8, M8 is one or more elements selected from the group consisting of Ti and Ge. ], (Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1-y9 M10 y9 )O4 [M9 is one or more elements selected from the group consisting of Mg, Al, Ga, and Zn, M10 is one or more elements selected from the group consisting of Zn, Al, Ga, Si, Ge, P, and Ti, 0≦x9≦1.0, 0≦y9≦0.6, a9 is the average valence of M9, and b9 is the average valence of M10], LiNb2O7, Li4Ti5O 12 , Li4Ti5PO12 , TiO2, LiSi, and graphite.

[0064] The negative electrode active material is preferably particulate. The 50% diameter in the volumetric particle size distribution, the aspect ratio, and the 50% diameter in the number-based particle size distribution of the primary particles in the case where the negative electrode active material forms secondary particles are preferably in the same range as those of the positive electrode active material.

[0065] The content of the negative electrode active material in the negative electrode active material layer is preferably 20% by mass or more, more preferably 30% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less. When the content of the negative electrode active material is within the above range, the negative electrode active material functions favorably, and a battery having a high energy density tends to be easily obtained.

[0066] ·Solid electrolyte The solid electrolyte that can be used in the negative electrode active material layer is not particularly limited, and any conventionally known solid electrolyte can be used. However, it is preferable to use the present oxide in order to better exhibit the effects of the present invention. The solid electrolyte used in the negative electrode active material layer may be one type or two or more types.

[0067] Additives Suitable examples of the conductive assistant include metal materials such as Ag, Au, Pd, Pt, Cu, and Sn, and carbon materials such as acetylene black, ketjen black, carbon nanotubes, and carbon nanofibers. As the sintering aid, a compound containing a boron atom, a compound containing a niobium atom, or a compound containing an M atom (examples of M: bismuth, silicon) is preferable. The additives used in the negative electrode active material layer may each be of one type or two or more types.

[0068] ·Negative electrode current collector As the negative electrode current collector, a current collector similar to the positive electrode current collector can be used.

[0069] <Manufacturing method for all-solid-state batteries> The all-solid-state battery can be formed, for example, by a known powder molding method. For example, a positive electrode collector, a powder for a positive electrode active material layer, a powder for a solid electrolyte layer, a powder for a negative electrode active material layer, and a negative electrode collector are stacked in this order and powder molded at the same time, so that the formation of each layer of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer, and the connection between each of the positive electrode collector, the positive electrode active material layer, the solid electrolyte layer, the negative electrode active material layer, and the negative electrode collector can be performed at the same time.

[0070] Suitable conditions for this powder molding include conditions (pressure, temperature) similar to those for sintering in the above-mentioned method for producing the present oxide.

[0071] The positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer may each be formed by powder molding. However, when an all-solid-state battery is produced using the obtained layers, it is preferable to press and sinter the layers.

[0072] The all-solid-state battery can also be produced, for example, by the following method. A paste for forming each layer is prepared by appropriately mixing a solvent, a resin, etc. with the material for forming the positive electrode active material layer, the material for forming the solid electrolyte layer, and the material for forming the negative electrode active material layer, and the paste is applied to a base sheet and dried to prepare a green sheet for the positive electrode active material layer, a green sheet for the solid electrolyte layer, and a green sheet for the negative electrode active material layer. Next, the green sheet for the positive electrode active material layer, the green sheet for the solid electrolyte layer, and the green sheet for the negative electrode active material layer, which are separated from the base sheet, are sequentially stacked, thermocompressed at a predetermined pressure, and then sealed in a container and pressed by a hot isostatic press, a cold isostatic press, a hydrostatic press, or the like, to prepare a laminated structure.

[0073] Thereafter, if necessary, this laminated structure is degreased at a predetermined temperature, and then sintered to produce a laminated sintered body. The sintering temperature in this sintering treatment is preferably the same as the sintering temperature in the method for producing the present oxide.

[0074] Next, if necessary, a positive electrode current collector and a negative electrode current collector can be formed on both main surfaces of the laminated sintered body by sputtering, vacuum deposition, coating or dipping with a metal paste, or the like, to produce an all-solid-state battery. EXAMPLES

[0075] Hereinafter, an embodiment of the present invention will be described in detail based on examples, although the present invention is not limited to these examples.

[0076] [Example 1] Lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, Merck, purity 99.0% or more), tantalum pentoxide (Ta2O5) (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., purity 99.9%), boric acid (H3BO3) (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., purity 99.5% or more), diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich, Merck, purity 98% or more), and lithium fluoride (LiF) (manufactured by Sigma-Aldrich, Merck) were weighed out so that the resulting lithium ion conductive oxide would satisfy the stoichiometric ratio (atomic number ratio) in Table 1. Specifically, taking into consideration the lithium atoms that flow out of the system during the firing process described below, lithium carbonate was weighed out in an amount 1.05 times the lithium atomic weight in Table 1, and diammonium hydrogen phosphate was weighed out in an amount 1.06 times the phosphorus atomic weight in Table 1 in order to suppress the generation of by-products during the firing process described below. At this time, the remaining elements to be weighed (tantalum, boron, and fluorine) were weighed out assuming that they would not flow out of the system at the firing temperature. An appropriate amount of toluene was added to each weighed raw material powder, and the mixture was ground and mixed for 2 hours using a zirconia ball mill (zirconia balls: diameter 5 mm) to obtain a primary mixture.

[0077] The obtained primary mixture was placed in an alumina boat and heated to 1000°C at a heating rate of 10°C / min in an air atmosphere (flow rate: 100 mL / min) using a rotary kiln (manufactured by Motoyama Co., Ltd.), and fired at that temperature for 4 hours to obtain a primary fired product.

[0078] An appropriate amount of toluene was added to the obtained primary fired product, and the mixture was ground and mixed for 2 hours using a zirconia ball mill (zirconia balls: diameter 1 mm) to obtain a secondary mixture. Using a tablet molding machine, the obtained secondary mixture was subjected to a pressure of 40 MPa using a hydraulic press to form a disk-shaped compact with a diameter of 10 mm and a thickness of 1 mm, and then pellets were produced by applying a pressure of 300 MPa to the disk-shaped compact using CIP (cold isostatic pressing).

[0079] The obtained pellets were placed in an alumina boat and heated to 850°C at a heating rate of 10°C / min in an air atmosphere (flow rate: 100 mL / min) using a rotary kiln (manufactured by Motoyama Corp.). The pellets were then sintered at that temperature for 96 hours to obtain a lithium ion conductive oxide (sintered body). The obtained lithium ion conductive oxide (sintered body) was cooled to room temperature, removed from the rotary sintering furnace, and transferred to and stored in a dehumidified nitrogen gas atmosphere.

[0080] [Examples 2 and 4] A lithium ion conductive oxide was produced in the same manner as in Example 1, except that the mixing ratio of the raw materials was changed so that the resulting lithium ion conductive oxide satisfied the stoichiometric ratio (ratio of the number of atoms) in Table 1.

[0081] [Examples 3, 5 and 6] A lithium ion conductive oxide was produced in the same manner as in Example 1, except that niobium pentoxide (Nb2O5) (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., purity 99.9%) was further used, and each raw material powder was used so that the resulting lithium ion conductive oxide satisfied the stoichiometric ratio (atomic number ratio) in Table 1.

[0082] [Comparative Example 1] Lithium carbonate (Li2CO3) (manufactured by Merck Sigma-Aldrich, purity 99.0% or higher), tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Corporation, purity 99.9%), and diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Merck Sigma-Aldrich, purity 98% or higher) were used in the same manner as in Example 1 except that the starting material powders were used such that the resulting lithium ion conductive oxide satisfied the stoichiometric ratio (atomic ratio) shown in Table 1 to produce a lithium ion conductive oxide.

[0083] [Comparative Example 2] Lithium fluoride (LiF) (manufactured by Merck Sigma-Aldrich) was further used, and a lithium ion conductive oxide was produced in the same manner as in Comparative Example 1 except that the starting material powders were used such that the resulting lithium ion conductive oxide satisfied the stoichiometric ratio (atomic ratio) shown in Table 1.

[0084] <X-ray diffraction (XRD)> The obtained lithium ion conductive oxide was pulverized using an agate mortar for 30 minutes to obtain a powder for XRD measurement. Using a powder X-ray diffractometer PANalytical MPD (manufactured by Spectris Co., Ltd.), the obtained powder for XRD measurement was subjected to X-ray diffraction measurement (Cu-Kα ray (output: 45 kV, 40 mA), diffraction angle 2θ = 10 to 50°, step width: 0.013°, incident side Soller slit: 0.04 rad, incident side anti-scatter slit: 2°, receiving side Soller slit: 0.04 rad, receiving side anti-scatter slit: 5 mm) to obtain an X-ray diffraction (XRD) pattern. The obtained XRD pattern was subjected to Rietveld analysis using known analysis software RIETAN-FP (which can be obtained from the homepage of its author Fujio Izumi, "RIETAN-FP·VENUS system distribution file" (http: / / fujioizumi.verse.jp / download / download.html)) to confirm the crystal structure contained therein and calculate the content rate (crystallinity) of each crystal structure. The results are shown in Table 2.

[0085] Moreover, the XRD patterns of the lithium ion conductive oxides obtained in Examples 2 and 3 and Comparative Example 1 are shown in FIG. 1, only the peaks derived from the monoclinic crystal structure of LiTa2PO8 were observed in Comparative Example 1. In the lithium ion conductive oxide obtained in Example 2, in addition to the peaks derived from the LiTa2PO8 structure, a peak derived from LiTa3O8 (ICSD code: 493) was observed, and in the lithium ion conductive oxide obtained in Example 3, in addition to the peaks derived from the LiTa2PO8 structure, a peak derived from Ta2O5 (ICSD code: 66366) was observed.

[0086] <Relative density> The mass of the lithium ion conductive oxide prepared was measured using an electronic balance. Next, the volume of the lithium ion conductive oxide was measured from its actual size using a micrometer. The measured mass was divided by the volume to calculate the density (actual density) of the lithium ion conductive oxide, and the relative density (%) was calculated as the percentage of the ratio of the actual density to the theoretical density of the lithium ion conductive oxide (actual density / theoretical density×100). The results are shown in Table 2. The theoretical value of the density of the lithium ion conductive oxide was calculated by taking a weighted average of the theoretical density of the crystal structure based on LiTa2PO8 and the theoretical density of the crystal structures based on LiTa3O8, Ta2O5, and TaPO5 (ICSD code: 202041) that constitute the lithium ion conductive oxide, using the content of each crystal structure obtained by Rietveld analysis.

[0087] <Total ionic conductivity> A gold layer was formed on both sides of the obtained lithium ion conductive oxide using a sputtering machine, thereby obtaining a measurement pellet for evaluating ion conductivity. The obtained measurement pellet was kept in a thermostatic bath at 25°C for 2 hours before measurement. Then, at 25°C, AC impedance measurement was performed in the frequency range of 1Hz to 10MHz at an amplitude of 25mV using an impedance analyzer (manufactured by Solartron Analytical, model number: 1260A). The obtained impedance spectrum was fitted to an equivalent circuit using the equivalent circuit analysis software ZView attached to the device to determine the lithium ion conductivity in the crystal grains and at the crystal grain boundaries, and the total ion conductivity was calculated by summing these. The results are shown in Table 2.

[0088] [Table 1]

[0089] The atomic ratios (stoichiometric ratios) and the contents of elements calculated by each formula in Table 1 are the atomic ratios (stoichiometric ratios) and the contents of elements calculated by each formula in the lithium ion conductive oxides obtained in each Example and Comparative Example.

[0090] [Table 2]

[0091] From Table 2, it is clear that this oxide has high total ionic conductivity and can easily produce a lithium ion conductive oxide with high relative density.

Claims

1. LiTa 2 P.O. 8 having a crystal structure based on At least lithium, tantalum, boron, phosphorus, oxygen and fluorine are contained as constituent elements, The content of boron represented by the following formula (1) is 4.0 to 15.0%, The content of fluorine represented by the following formula (2) is 0.5 to 2.0%. Lithium ion conducting oxide. Number of B atoms / (Number of B atoms + Number of P atoms) × 100 (1) Number of F atoms / (number of O atoms+number of F atoms)×100 (2)

2. Further, it has niobium as a constituent element, The niobium content represented by the following formula (3) is more than 0% and 20.0% or less. The lithium ion conductive oxide according to claim 1 . Number of Nb atoms / (number of Nb atoms+number of Ta atoms)×100 (3)

3. 3. The lithium ion conductive oxide according to claim 1, wherein the relative density, which is a percentage of a ratio of an actual density calculated from the mass and volume of the oxide to a theoretical density of the lithium ion conductive oxide, is 70% or more.

4. The LiTa 2 P.O. 8 The lithium ion conductive oxide according to any one of claims 1 to 3, wherein the content of the crystal structure based on the formula (I) is 85% or more.

5. The content of lithium represented by the following formula (4) is more than 0.9 and not more than 1.5, The lithium ion conductive oxide according to any one of claims 1 to 4. Number of Li atoms / {(number of Nb atoms+number of Ta atoms) / 2} (4)

6. a positive electrode having a positive electrode active material; a negative electrode having a negative electrode active material; a solid electrolyte layer between the positive electrode and the negative electrode; Including, The solid electrolyte layer comprises the lithium ion conductive oxide according to any one of claims 1 to 5. All-solid-state battery.

7. The positive electrode active material is LiMPO 4 [M3 is one or more elements selected from the group consisting of Mn, Co, Ni, Fe, Al, Ti and V, or two elements selected from V and O.], LiM5VO 4 [M5 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al and Ti.], Li 2 M6P 2 O 7 [M6 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al, Ti and V, or two elements selected from V and O.], LiVP 2 O 7 , Li x7 V y7 M7 z7 [2≦x7≦4, 1≦y7≦3, 0≦z7≦1, 1≦y7+z7≦3, M7 is one or more elements selected from the group consisting of Ti, Ge, Al, Ga, and Zr.], Li 1+x8 A x8 M8 2-x8 (P.O. 4 ) 3 [0≦x8≦0.8, M8 is one or more elements selected from the group consisting of Ti and Ge. ], LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 , LiCoO 2 , LiNiO 2 , LiMn 2 O 4 , Li 2 CoP 2 O 7 , Li 3 V 2 (P.O. 4 ) 3 , Li 3 Fe 2 (P.O. 4 ) 3 , LiNi 0.5 Mn 1.5 O 4 and Li 4 Ti 5 O 12 The all-solid-state battery according to claim 6, comprising one or more compounds selected from the group consisting of:

8. The negative electrode active material is LiMPO 4 [M3 is one or more elements selected from the group consisting of Mn, Co, Ni, Fe, Al, Ti and V, or two elements selected from V and O.], LiM5VO 4 [M5 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al and Ti.], Li 2 M6P 2 O 7 [M6 is one or more elements selected from the group consisting of Fe, Mn, Co, Ni, Al, Ti and V, or two elements selected from V and O.], LiVP 2 O 7 , Li x7 V y7 M7 z7 [2≦x7≦4, 1≦y7≦3, 0≦z7≦1, 1≦y7+z7≦3, M7 is one or more elements selected from the group consisting of Ti, Ge, Al, Ga, and Zr.], Li 1+x8 A x8 M8 2-x8 (P.O. 4 ) 3 [0≦x8≦0.8, M8 is one or more elements selected from the group consisting of Ti and Ge. ], (Li 3-a9x9+(5-b9)y9 M9 x9 ) (V 1-y9 M10 y9 ) O 4 [M9 is one or more elements selected from the group consisting of Mg, Al, Ga, and Zn, M10 is one or more elements selected from the group consisting of Zn, Al, Ga, Si, Ge, P, and Ti, 0≦x9≦1.0, 0≦y9≦0.6, a9 is the average valence of M9, and b9 is the average valence of M10], LiNb 2 O 7 , Li 4 Ti 5 O 12 , Li 4 Ti 5 P.O. 12 , TiO 2 8. The all-solid-state battery according to claim 6, further comprising one or more compounds selected from the group consisting of LiSi, LiSi, and graphite.

9. The all-solid-state battery according to any one of claims 6 to 8, wherein the positive electrode and the negative electrode contain the lithium ion conductive oxide according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Composite solid electrolyte, preparation method thereof and lithium ion battery

    CN111403805A

  • Lithium ion conductive solid electrolyte

    JP2013157090A

  • Solid conductor, manufacturing method thereof, solid electrolyte including the same, and electrochemical element

    JP2020194773A

  • Ion-conductive solid electrolyte compound, method for preparing same, and electrochemical device comprising same

    WO2020036290A1

  • Lithium ion-conducting oxide

    WO2021039834A1